Decoupling and attribution analysis of industrial carbon emissions in Taiwan. (15th October 2016) - Wang, Qunwei; Hang, Ye; Zhou, P.; Wang, Yizhong
Abstract: A deeper understanding of the decoupling status between carbon emissions and industrial growth as well as its influencing factors is very important in implementing targeted polices. This study applies decoupling analysis, index decomposition analysis, and attribution analysis to achieve three goals. First, the study explores the decoupling relationship between industrial growth and carbon emissions in Taiwan. Second, the factors influencing changes in industrial carbon intensity are explored. Finally, the contributions of industrial sub-sectors to each factor are analyzed. The results indicate that Taiwan's industrial growth and carbon emissions experienced a negative decoupling from 2007 to 2009 and a decoupling from 2009 to 2013. Energy intensity effect plays the dominant role in promoting decoupling, and both energy structure effect and industrial structure effect negatively impact decoupling. The chemical materials, electrical and electronic machinery and basic metal industries sub-sectors are primarily responsible for the energy intensity effect. Energy-intensive industries are the main contributors to the increase in energy structure and industrial structure effects. The study suggests that the Taiwanese government should establish targeted carbon reduction measures at sub-sector level. Adjusting the energy structure and industrial structure is also urgently required to promote the decoupling of carbon emissions from industrial growth. Highlights: The decoupling relationship of industrial growth and carbon emissions was explored. The factors influencing changes in industrial carbon intensity were explored. The contributions of industrial sub-sectors to each factor were analyzed. Energy intensity effect played the dominant role in promoting decoupling. The sub-sector contributions to different influencing factors varied significantly.